Religious Authority in Social Media: The Influence of Ali Jum`ah's Online Fatwa (b. 1953 AD) and Yusuf al-Qaradawi (b. 1926 AD - d. 2022 AD) - Fikri, Ali; Abdullah , Amin; Sunarwoto, Sunarwoto (AL-TAHRIR, 2024)
The inevitable rise of modernity means that clerics will lose their role and will no longer be autonomous. Nevertheless, as a new way to maintain their position in society and strengthen their authority, it is not uncommon for them (ulama) to use technological advances to record fatwas and advice delivered to the public. This study examines several fundamental issues concerning how Ali Jum`ah and Yusuf al-Qaradhawi build their religious authority through new media, and to what extent new media plays a role in increasing their religious authority. This research found the way the two figures built their religious authority through new media. Ali Jum`ah built his religious authority through new media when he led Dar al-Ifta. He turned Dar al-Ifta into a modern global institution based on new media. Meanwhile, al-Qaradhawi built his religious authority through new media by cooperating with experts and various professionals in the field of media, one of them being through the Qatar-based al-Jazeera TV channel. The power and role of new media utilized by the two figures were able to mobilize an unprecedented number of people, thus strengthening their authority. This research contributes to producing new knowledge about the emergence of Islamic public space through the presence of new media in the Islamic world as an effort to stimulate and expand the movement of ijtihad that is more responsible and more effective in this contemporary era.